Ring opening reactions of tetrathiacyclopropenonophanes and the subsequent formation of a molecular box stabilised by hydrogen bonds - Werz, Daniel B.; Rominger, Frank; Gleiter, Rolf (Arkivoc)
Sulfur atoms next to a cyclopropenone moiety change their reactivity completely. Tetrathiacyclopropenonophanes 6 and 10 were treated with protic solvents such as methanol and water yielding ring opened diesters 9a and 9b, and the diacid 11, respectively. This observation is in contrast to alkyl and aryl substituted cyclopropenones which are stable in the presence of protic solvents. The molecular structures of the diester and the diacid could be elucidated by means of X-ray diffraction analyses. In the latter case a molecular box was formed in such a way that the two acid moieties dimerise via hydrogen bonding. The resulting hollow core is able to host one molecule of chloroform.
Dedicated to Prof. Nikolay Zefirov on the occasion of his 70th birthday
Gesehen am 21.10.2020
Keywords: Festschrift